Incentive Spirometer Versus Diaphragmatic Breathing On Ventilatory Function And Quality Of Life In Patients With Interstitial Lung Diseases. A Randomized Controlled Trial (International Journal of Environmental Sciences, 2025)
Background and purpose: Interstitial lung diseases (ILDs) remain major causes of mortality. This trial aimedcompare the effects of incentive spirometer (IS) and diaphragmatic breathing exercise (DBE) on ventilatory function, functional capacity, dyspnea, and quality of life (QoL) in patients with ILDs.Material and methods: Sixty male patients with ILDs were assigned randomly into 3 equal groups. Through 8 weeks, IS group received IS training and aerobic exercises (AEs); DBE group received DBE and AEs, while the control group received AEs only. Forced expiratory volume in the first second (FEV1), forced vital capacity (FVC) and FEV1/FVC were assessed using an electronic spirometer, functional capacity using six-minute walk teat (6MWT), dyspnea using dyspnea-12 questionnaire (D-12), and QoL using 12-item short form health survey (SF-12).Results: Compared to the control group, significant between-group differences were observed in FVC (IS: MD= 4.22%, CI 95%= 1.58 to 6.86, p= 0.004; DBE: MD= 4.2%, CI 95%= 1.24 to 7.16, p= 0.002), FEV1 (IS: MD= 3.3%, CI 95%= 0.19 to 6.41, p= 0.03; DBE: MD= 4.01%, CI 95%= 0.76 to 7.26, p= 0.01), 6MWT distance (IS: MD= 14.25 m, CI 95%= 1.96 to 26.54, p= 0.02; DBE: MD= 12.05 m, CI 95%= 0.39 to 23.71, p= 0.04), D-12 scores (IS: MD= –3.07, CI 95%= –5.87 to –0.27, p= 0.02; DBE: MD= –3.54, CI 95%= –6.52 to –0.56, p= 0.01),and SF-12 physical (IS: MD= 4.97, CI 95%= 0.03 to 9.91, p= 0.02; DBE: MD= 4.06, CI 95%= –0.37 to 8.49, p= 0.04) and mental (IS: MD= 3.73, CI 95%= –1.08 to 6.38, p= 0.02; DBE: MD= 4.4, CI 95%= 1.62 to 7.18, p= 0.007) component scores, at post-study. No significant differences were observed between IS and DBE groups in any outcome (p > 0.05).Conclusions: BothIS and DBE can similarly improve ventilatory function, functional capacity, dyspnea and QoL in ILDs male patients.